The domain name registration system : liberalization, consumer protection and growth - Ng, Jenny; ebrary, Inc. (London : Routledge, 2013)
This book offers a comparative analysis of the domain name registration systems in Australia and the United Kingdom. It analyses global trends and international perspectives of domain name registration systems and the dynamics in the respective domain name systems. The research project explores the advantages and disadvantages of the restrictive domain name registration system and the less restrictive registration system by addressing issues of consumer protection and promoting growth in the number of domain name registrations. The book analyses several different types of domain name registration systems and analyses the regulatory frameworks in the restrictive and unrestrictive registration systems. It considers recent developments in this area such as the new transfer rules in Australia which allows for the sale of domain name licence, the new Business Name Registration rules due to enter into force in 2011 in Australia, and the new policy rules on domain name dispute resolution in the United Kingdom. Jenny Ng also examines the legal and economic implications of these regulatory frameworks, drawing upon economic theory, regulatory and systems theory as well as legal analysis and comparison of regulatory frameworks. In doing so the work puts forwards ways in which such systems could be better designed to reflect the needs of the specific circumstances in individual jurisdictions
pt. 1. The domain name registration system : overview and international perspectives -- pt. 2. Comparative analysis : consumer protection and growth in domain name registrations in the United Kingdom and Australia.
Obsahuje bibliografii a rejstřík
Elektronická reprodukce.
Keywords: doménová jména; ochrana spotřebitele; Internet domain names; consumer protection; Austrálie; Velká Británie; Australia; Great Britain; e-knihy online; e-books online